1996
DOI: 10.1177/014107689608901209
|View full text |Cite
|
Sign up to set email alerts
|

Educating Psychiatric Patients about their Treatment: Do Fact Sheets Work?

Abstract: Psychiatric patients are sometimes given fact sheets about their treatment but the benefits of these are uncertain. We tested three strategies in three cohorts of psychiatric inpatients--fact sheets alone, fact sheets and subsequent discussion, and control. Knowledge of medication was assessed by questionnaire. For various reasons, only 33 of the 77 patients were included in the study or analysis. Of the patients who had been given fact sheets, 87% independently read them and reported finding them helpful whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 4 publications
0
30
0
2
Order By: Relevance
“…All six trials reported that patients who received education demonstrated an increased knowledge relating to illness and medication when compared with their baseline scores. These findings were statistically significant in only four trials (Chaplin & Kent 1998; Evans et al . 1996; Macpherson et al .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…All six trials reported that patients who received education demonstrated an increased knowledge relating to illness and medication when compared with their baseline scores. These findings were statistically significant in only four trials (Chaplin & Kent 1998; Evans et al . 1996; Macpherson et al .…”
Section: Resultsmentioning
confidence: 95%
“…The knowledge level was assessed using tools such as the education effect score, medication education questionnaire (Angunawela & Mullee 1998; Dow et al . 1991; Evans et al . 1996; Goulet et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations